(untitled) (Bangladesh Medical Journal, 2014)
The objective of this cross-sectional study was to assess the health-related quality of life among adult migrant garment workers (age 18-59 years) in Dhaka city. The study was conducted with 400 workers for quantitative research, and two health care service providers for qualitative research. Data were collected during February to March 2009. Data were collected by face-to-face interviews using a constructed pre-tested questionnaire adapted from WHOQOL-BREF. Data were analyzed by applying descriptive statistics (frequency, percentage, mean, standard deviation, range and median) and inferential statistics (unpaired ttest and oneway ANOVA) to examine the relationship between health-related quality of life and socio-demographic characteristics, living and working conditions, and accessibility to health care services. Statistical significance was set as p<0.05. The results revealed that 94.00% of workers reported low level of health-related quality of life. The rest were moderate and high, 3.25% and 2.75% respectively. For socio-demographic characteristics, workers’ marital status, having family members, income, history of sickness and getting treatment when sick were discovered to have association with health-related quality of life. For living and working conditions, workers’ living place, work permit, length of current job and satisfaction on work conditions were significantly associated with health-related quality of life. For accessibility to health care services, perception on difficulty to go to the health facility, crowdedness of the health facility and having health insurance card were found to be associated with health-related quality of life. Further longitudinal researches and policies are recommended to improve access to health care services and higher health-related quality of life for migrant garment workers in Dhaka city. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18651 Bangladesh Medical Journal 2011 Vol.40(3):14-17